Edukasi dan Pelatihan Tanaman Herbal, Teh Rosella Untuk Mengatasi Hipertensi (Darah Tinggi) di Masyarakat [Education and Training on Herbal Plants, Rosella Tea, to Treat Hypertension (High Blood Pressure) in the Community] - Kurniawati, Darini; Irpiana, Irma; Kiptiyah, Mariyatul; Alfisah, Firda; Daud, Muhammad Alfian (Indonesia Berdaya, 2026)
Hypertension or high blood pressure is one of the non-communicable diseases that is the leading cause of premature death in the world, which if left untreated can trigger serious complications such as heart disease and stroke. One alternative non-pharmacological treatment that is starting to be widely developed in the community is the use of the herbal plant Rosella (Hibiscus sabdariffa). The objectives and focus of this activity are: Increase public knowledge about the dangers of hypertension, Provide education about the content of anthocyanin compounds in Rosella flowers that function as natural ACE-inhibitors and diuretics, Provide training on how to process dried Rosella flower petals into a safe brewed tea, and introduce the correct dosage to avoid side effects for the stomach. There was an 83,75% increase in public knowledge about complementary therapies after the counseling. The community is now able to independently process Rosella tea as a family health drink that is economical and effective in helping to maintain stable systolic and diastolic blood pressure. Abstrak. Hipertensi atau tekanan darah tinggi merupakan salah satu penyakit tidak menular yang menjadi penyebab utama kematian dini di dunia, yang jika tidak ditangani dapat memicu komplikasi serius seperti penyakit jantung dan stroke. Salah satu alternatif pengobatan non-farmakologis yang mulai banyak dikembangkan di masyarakat adalah pemanfaatan tanaman herbal Rosella (Hibiscus sabdariffa). Tujuan dan fokus kegiatan ini adalah untuk: Meningkatkan pengetahuan masyarakat mengenai bahaya hipertensi, Memberikan edukasi mengenai kandungan senyawa antosianin dalam bunga Rosella yang berfungsi sebagai ACE-inhibitor alami dan diuretik, Memberikan pelatihan cara pengolahan kelopak bunga Rosella kering menjadi teh seduhan yang aman dikonsumsi, serta mengenalkan dosis penggunaan yang tepat agar tidak menimbulkan efek samping bagi lambung. Terdapat peningkatan pengetahuan masyarakat mengenai terapi komplementer sebesar 83,75% setelah dilakukan penyuluhan. Masyarakat kini mampu secara mandiri mengolah teh Rosella sebagai minuman kesehatan keluarga yang ekonomis dan efektif dalam membantu menjaga kestabilan tekanan darah sistolik dan diastolik.